Impact of heavy metals and metalloids on soil microorganisms of mining areas - Moreira, H. (2017)
Soil is a non-renewable resource that plays a key role in sustaining life. However, soils’ degradation has increased in the last decades due anthropogenic activities leading to the loss of their functions and ecosystems services. Mining operations are one of the majors soil disruptors and are associated with a broad range of environmental negative impacts, including the decline of soils’ quality over large areas. The release of hazardous compounds, such as heavy metals and metalloids, during the extraction and processing of mineral ores leads to long-term contamination and hampers the survival of soil-associated microorganisms. The microbial diversity and activity in such polluted soils is disturbed causing negative cross-effects in the ecosystems, as soil microorganisms play a significant role in nutrient recycling and in biogeochemical cycles. Although microbial redundancy may occur and some microorganisms reveal resistance or tolerance mechanisms, the simplification of microbial communities and the subsequent decrease in their activity can lead to the failure of general soil functions. In this review the effects of mining-generated heavy metals and metalloids on soil microbial activities and composition are discussed. Soil microbiological and biochemical properties such as biomass, enzyme activity, respiration and communities’ shifts commonly found in these areas are addressed and the general impact of these microbial modifications in the soil functions is underlined.